THE TEACHER-STUDENT RELATIONSHIP INSIDE THE CLASSROOM AS A SPACE OF ETHICAL FORMATION IN THE UNIVERSITY - Vélez Valcárcel, Odette (2006)
The present article is the synthesis of an investigation realized during the second year of studies of the PHD program of "Education and democracy" of the University of Barcelona, which had as main aim to explore the relationship teacher-student inside the class as a space of ethical formation in the university. It starts by raising some theoretical considerations on the ethical formation and on the teacher-student relationship, for then contextualize them within the university area.. This way, having recognized education as an inevitably ethical event, it indicates that education in values not only is given across the formal areas of the educational institutions but also from it’s formal and informal areas. Once having put attention in these less planned spaces of moral formation, the need to appeal to values experience is enhanced to achieve that ethical learning becomes really significant. From these ideas, the interpersonal area, and specifically the teacher–student relationship inside the classroom, appears as a space of ethical formation that needs to be taken in advantage, even more at the university, where education in values is raised from isolated subjects that prioritize conceptual contents. Finally, they present methodological aspects of the investigation and some commentaries about the results obtained from it.